Case Report: Improvement of functional dyspepsia using eight constitution acupuncture and eight constitution diet – A report of three cases - Nahyun Cho; Nahyun Cho; Younkuk Choi; Younkuk Choi; Heekyung Kim; Heekyung Kim; Heeyoung Moon; Younbyoung Chae; Sungha Kim; Jungtae Leem; Jungtae Leem; Jungtae Leem (Frontiers in Medicine, 2025)
BackgroundFunctional dyspepsia (FD) is a common gastrointestinal disorder affecting 10–20% of the global population. This case series aimed to report the clinical outcomes of three patients with FD who were treated with eight constitution acupuncture (ECA) and eight constitution diet (ECD), a personalized treatment approach based on the eight constitution medicine (ECM) theory.MethodsThree patients with chronic FD were retrospectively selected from two Korean medical clinics. Each patient underwent ECA and ECD according to their constitution type as determined by pulse diagnosis. FD symptoms and quality of life were assessed using the Nepean Dyspepsia Index-Korean version (NDI-K) and Functional Dyspepsia-Quality of Life (FD-QoL) scores before and 2 and 4 weeks post-treatment. Adherence to treatment and adverse events were also evaluated.ResultsAll three patients showed significant improvements in NDI-K and FD-QoL scores after 4 weeks of treatment. No adverse events were observed during the treatment period. In particular, one patient experienced temporary symptom relapse due to poor dietary adherence, suggesting that the effectiveness of ECD may be associated with adherence to the prescribed diet.ConclusionECA combined with ECD led to significant symptom improvement and improved the quality of life in patients with chronic FD. These findings support the potential use of ECM-based interventions as effective and personalized treatment approaches for FD. More studies with larger sample sizes and standardized tools to assess diet adherence are required to validate these results and explore long-term outcomes.